2001
DOI: 10.1111/j.1542-474x.2001.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Documentation of Arrhythmias after Successful Radiofrequency Catheter Ablation of Accessory Pathways

Abstract: 94% patients with a long history of tachyarrhythmias due to the WPW syndrome reported improved physical well-being after ablation, but palpitations were common during a 2-year follow-up period; 8% continued to use pharmacological antiarrhythmic treatment. Five percent had symptomatic relapses and in 6% atrial fibrillation episodes reoccurred, i.e., in half of those who had atrial fibrillation before ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…We, therefore, assume that the reported episodes of syncope and/or near‐syncope were not exaggerated, but rather were underestimated. On the other hand, the figures are in the same range as in the work by Woods 7 and our own previous investigation 8 …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We, therefore, assume that the reported episodes of syncope and/or near‐syncope were not exaggerated, but rather were underestimated. On the other hand, the figures are in the same range as in the work by Woods 7 and our own previous investigation 8 …”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the figures are in the same range as in the work by Woods 7 and our own previous investigation. 8 In this study, the use of class IC antiarrhythmic drugs was associated with a higher rate of occurrence for syncope, but the reason for this is unknown. No case of documented ventricular tachycardia was found that would indicate a proarrhythmic effect.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…9 However, there are studies indicating that patients treated successfully with RFA still experience symptoms of arrhythmia during follow-up. 19,32 Long-term HRQOL follow-up gives valuable information about treatment outcome and the life situation after ablation. Overall, there are few studies available comparing these patients with a normative population, and the comparisons made so far were done before RFA.…”
Section: Discussionmentioning
confidence: 99%
“…The third beat either is a junctional beat or represents anterograde conduction down a slow pathway (2) to the ventricle. Activation then travels down the bundle branch (3) and retrogradely to the atria through a left lateral bypass tract (4).…”
Section: Commentarymentioning
confidence: 99%